2019
DOI: 10.1029/2019gl085385
|View full text |Cite
|
Sign up to set email alerts
|

Decadal Predictions of the Probability of Occurrence for Warm Summer Temperature Extremes

Abstract: We use a decadal prediction system with the Coupled Model Intercomparison Project Phase 6 version of the coupled Max Planck Institute Earth System Model to predict the probability of occurrence for extremely warm summers in the Northern Hemisphere. An assimilation run with Max Planck Institute Earth System Model shows a robust response of summer temperature extremes in northern Europe and northeast Asia to North Atlantic sea surface temperature via a circumglobal Rossby wavetrain. When the North Atlantic is wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
0
17
2
Order By: Relevance
“…These results stand in contrast to modelling studies e.g. from CMIP6 suggesting a 0 to 8% probability for heat waves following cold surface temperatures (Borchert et al, 2019) or single-event attributions which show a small or no surface temperature control (Wehrli et al, 2019).…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…These results stand in contrast to modelling studies e.g. from CMIP6 suggesting a 0 to 8% probability for heat waves following cold surface temperatures (Borchert et al, 2019) or single-event attributions which show a small or no surface temperature control (Wehrli et al, 2019).…”
contrasting
confidence: 99%
“…There is currently no consensus on the mechanisms causing the sudden increase in major European heat waves in recent decades. One possible mechanism, although its robustness is yet uncertain (Borchert et al, 2019), suggested that most major heat waves/droughts during this period appear to be linked with unusually cold North Atlantic sea-surface temperatures (e.g. Duchez et al, 2016) possibly due to a slowdown of the Atlantic Meridional Overturning Circulation (e.g.…”
mentioning
confidence: 99%
“…3A), which might influence heat wave occurrence over Europe, as suggested recently for the 2015 cooling event in the SPG, 28,29 although this remains under debate. 30 Figure 4 depicts the three-model ensemble mean response to cooling events in terms of precipitation. It shows a relatively clear southward shift of the Intertropical Convergence Zone (ITCZ) over the Atlantic sector for both summer and winter seasons.…”
Section: Climatic Impacts Of the Abrupt Cooling Eventsmentioning
confidence: 99%
“…We present results for the combination of 4 lagged forecasts, but find similar levels of skill for other combinations (NAO ACC = 0.71 and 0.78 for combining 3 and 5 lagged forecasts respectively). A similar technique relying on persistence of the predictor recently proved to strongly reduce the noise in decadal predictions of summer temperature extremes over land 62 .…”
Section: Ratio Of Predictable Components Rpcmentioning
confidence: 99%